The political impacts of adaptation actions: Social contracts, a research agenda. (31st August 2018) - Blackburn, Sophie; Pelling, Mark
Abstract : Managing climate and disaster risk is a deeply political act sitting at the interface of popular expectations, legal mandate, and political fiat. This article makes the case for an expanded research agenda on social contracts in climate and disasters scholarship as a mechanism to better reveal activity across this interface, identify the winners and losers of adaptation, and improve the equity outcomes of negotiated and imposed risk management settlements. Social contracts are defined as multiple and constructed (not singular or fixed), and three distinct yet intersecting forms of social contracts are identified: imagined, practiced, and legal‐institutional. The article argues that mapping the disjunctures, overlaps and transitions between these concurrent social contracts can help reveal gaps between responsibilities held de facto and de jure . This makes a timely contribution to understanding tensions between need, obligation and entitlement that underlie contestations over "who" is responsible for "what" in risk governance. It also helps reveal the dynamic boundaries of social acceptances at the centre of debates around fair adaptation governance. Such work can provide insight on how development relations, including but reaching beyond risk management and climate change adaptation, can be transformed progressively and fairly in a changing climate. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract :